ANALISI HUBUNGAN MAGNITUDO GEMPA BUMI TERHADAP HASIL FREKUENSI DOMINAN PADA RANGKAIAN GEMPA ACEH 2004, YOGYAKARTA 2006, PALU DAN LOMBOK 2018 SEBAGAI UPAYA MITIGASI BENCANA - Nela Elisa Dwiyanti; Vira Irnanda, Elleona Septi N; Indriati Retno Palupi; Wiji Raharjo; Wrego Seno Giamboro; Afriliani M Handini; Ananda Achlaqul Karimah; Ririn Setyowati; Edoarddo Tobing (Unit Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Meteorologi Klimatologi dan Geofisika, 2020)
Indonesia is located at the boundaries of three major plate of the world, namely Indo-Australia, Eurasia, and the Pacific Plates. This has made Indonesia prone to earthquakes, so mitigation are needed. The purpose of this research is to determine the empirical relationship between earthquake magnitude and dominant frequency results based on several major earthquake events in Indonesia such as in Aceh 2004, Yogyakarta 2006, Lombok and Palu 2018 as an effort to earthquake hazard mitigation in Indonesia. Magnitude carries information about earthquake power based on the energy released from the hypocenter. Physically, magnitude is related to frequency. The frequency can obtained from earthquake records in time domain which are converted to frequency domain by Fast Fourier Transform method. Earthquake data is obtained from IRIS and uses 89 events with magnitude of 4-9. In Aceh, Yogyakarta, Lombok, and Palu that relatioship between magnitude and frequency are y = -0.053x + 6.2999, y = 0.018x + 4.082, y = -0.0496x + 6.455, and y = -0.0192x + 5.3129. In this research, it can be concluded that the bigger magnitude of the earthquake has smaller frequency. The potential magnitude that appear if the seismicity are low in Aceh, Yogyakarta, Lombok, and Palu are 6.2, 4, 6.4, and 5.3.